Changes in blindness prevalence over 16 years in Malawi: reduced prevalence but increased numbers of blind - Courtright, P (Copyright 2003 British Journal of Ophthalmology, 2003)
Background/aims: In the coming two decades significant increases in the burden of blindness are anticipated unless concerted efforts are made to improve eye care in developing countries. Evidence of changing prevalence rates or numbers of blind people are few. The change in blindness prevalence and the number of blind people in an adult population of Malawi was measured over a 16 year period. Methods: In 1999 a population based survey of blindness in adults (age 50+) was conducted in Chikwawa district of Malawi. Visual acuity and cause of vision loss were recorded for each eye independently. Blindness was defined as presenting better eye vision of <6/60. Findings from a 1983 survey of blindness in the same district (using similar methods) were re-analysed to be comparable with the survey conducted in 1999. Results: Among 1630 enumerated adults 89% were examined. The age adjusted prevalence of blindness in the adult population was 5.4% and more common in women than men. In each age group the prevalence of blindness was lower in 1999 than in 1983; the overall reduction in blindness was 31%. During this period the 50+ population in Malawi increased almost twofold. Extrapolating the Chikwawa district data to the Malawi population reveals that the number of blind people has increased by 24%; the increase is primarily because of the large increase in the size of the most elderly group, aged 70 and above. Conclusion: The majority of blind people in Chikwawa (1983 and 1999) are in the age group 70 and over. This group has had the largest proportional increase in population size in this time. Services in this population have improved in the intervening 16 years and yet there was still an increase in the number of blind people. There was little change in excess blindness in women, suggesting that the same barriers that prevented utilisation of services in 1983 probably persist in 1999. Efforts to reach the most elderly and to reach women are needed to lead to a reduction in blind people in settings such as rural Malawi.